Determinasi Tax Avoidance : Peran Thin Capitalization dan Karakter Eksekutif Pada Sektor Transportasi - Arisani, Mega Dewi; Widiatmoko, Jacobus (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Tax avoidance is an effort to reduce tax burdens in order to maximize profits in accordance with tax regulations. The purpose of this study is to confirm and collect empirical data on the impact of executive characteristics and thin capitalization on tax avoidance in the transportation sector listed on the IDX between 2020 and 2024. This study uses quantitative data. Through purposive sampling, a total of 275 samples were obtained from 55 transportation sector companies listed on the IDX between 2020 and 2024. This study uses secondary data as its data type. Using multiple linear regression analysis, the research findings show that thin capitalization, company size, and profitability have a significant positive effect on tax avoidance in transportation sector companies listed on the IDX for the years 2020-2024. Meanwhile, executive characteristics and sales growth do not significantly influence tax avoidance in transportation sector companies listed on the IDX for the years 2020-2024.